Determination of The Mineral Composition of Foam-Mat Dried Ngu Powder Using Response Surface Methodology - Maduebibisi Ofo Iwe; Emmanuel Uduma; Anna Ngozi Agiriga (Food ScienTech Journal, 2024)
Foam-mat drying of Ngu using egg white as a foaming agent was investigated. Three concentrations of Ngu sample- 60, 80, and 100% were used for the study. The Ngu samples were enriched with egg white at 20, 25, and 30% concentration respectively at room temperature. The mixture was beaten for 5, 9, and 12 mins. A central composite response surface design was employed to investigate the impact of whipping duration, egg white, and Ngu concentration on the mineral composition of dried Ngu powder. Regression models showed that the experimental variables had significant (p<0.05) effects on the dry Ngu powder's iron, zinc, calcium, sodium, phosphorus, potassium, and magnesium contents. The optimal values for all responses were achieved using a combination of 10 mins of whipping time, 20.8% egg white, and 100% Ngu concentration. The optimal values for the mineral content of Ngu powder were determined to be 17.46 mg/g for iron, 1.03mg/g for zinc, 0.58 mg/g for calcium, 12.72 mg/g for sodium, 2.26 mg/g for phosphorus, 1.36 mg/g for potassium and 0.26 mg/g for magnesium.